2009
DOI: 10.1159/000261503
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Auto-Immune Pemphigus in the Midi-Pyrénées Region in 2002–2006

Abstract: Introduction: Auto-immune pemphigus is an organ-specific immune disorder due to pathogenic auto-antibodies. Both genetic and environmental factors have been associated with the occurrence of auto-immune pemphigus. Little is known about the epidemiology of auto-immune pemphigus in western Europe. Objective: To evaluate the incidence of auto-immune pemphigus in south-western France (namely the Midi-Pyrénées region) in a 5-year period between 2002 and 2006. Materials and Methods: We performed a retrospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
1
6
1
2
Order By: Relevance
“…This first epidemiological study about autoimmune pemphigus in the Afro‐Caribbean population showed a high world‐population‐standardized incidence of 6.96 cases per million inhabitants per year (95% CI: 2.97–10.97). This incidence rate is higher than that reported in the USA and in Western Europe, where the incidence rate varies from 0.6 to 1.55 cases per million inhabitants per year according to the most recent studies . It is also greater than world‐population‐standardized incidence rates reported in studies performed in the Mediterranean Basin, where values are the highest (i.e.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…This first epidemiological study about autoimmune pemphigus in the Afro‐Caribbean population showed a high world‐population‐standardized incidence of 6.96 cases per million inhabitants per year (95% CI: 2.97–10.97). This incidence rate is higher than that reported in the USA and in Western Europe, where the incidence rate varies from 0.6 to 1.55 cases per million inhabitants per year according to the most recent studies . It is also greater than world‐population‐standardized incidence rates reported in studies performed in the Mediterranean Basin, where values are the highest (i.e.…”
Section: Discussioncontrasting
confidence: 55%
“…Moreover, various epidemiological studies have identified environmental antigens linked to endemic PF . For these reasons, annual incidence of the disease differs among ethnic groups and in parts of the world . Little is known about the epidemiology of autoimmune pemphigus in black patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cette disparité serait probablement liée à des facteurs génétiques et environnementaux. En Occident, Asie et en Amérique latine, les particularités des pemphigus ont été bien caractérisées [3][4][5][6][7][8][9][10][11]. Par contre, en Afrique noire, l'étude des pemphigus a été souvent limitée par la Aspects epidemiologiques et cliniques des pemphigus Aspects epidemiologiques et cliniques des pemphigus au Senegal au Senegal non disponibilité des examens complémentaires, surtout des l'immunofluorescences, indispensables au diagnostic [12][13][14].…”
Section: Introductionunclassified